Evaluation of capability of ultrasound with elastometry and elastography for diagnosis of subclinical regional metastases of cancer of the oral mucosa - Yu. V. Alymov (Опухоли головы и шеи, 2017)
Objective. Evaluation of ultrasound capabilities for diagnosis of subclinical regional metastases of squamous cell carcinoma of the oral mucosa.Introduction. Incidence of oral cancer in Russia is 3.86 per 100,000 population, and it’s increasing with the mean annual rate of 1.88 %. Head and neck cancer is characterized by high risk of metastases in regional lymph nodes which varies from 40 to 80 %. Lymph nodes status affects the treatment plan and appears to be the main predictive factor. Therefore, evaluation of the pathways of regional lymphatic outflow in oral mucosa cancer is of prime importance for disease prognosis and treatment selection. Ultrasound investigation (USI) is one of the main instrumental methods of regional lymph node investigation in oral mucosa cancer patients. Nevertheless, effectiveness of B-mode USI, elastometry and elastography for diagnosis of occult metastases of squamous cell carcinoma of the oral mucosa has not been investigated. There is no consensus on the threshold values of S-wave velocity and elastographic parameters in diagnosis of occult metastases.Materials and methods. Patients with oral mucosa squamous cell carcinoma (stage cT1–3N0M0) were included in the study. All patients had morphologically verified diagnosis. At the first stage (outpatient) before inclusion into the study, all patients were evaluated by palpation and B-mode USI. If during USI metastases were suspected, FNAB was performed. Patients with cytologically confirmed metastases were not eligible for the study. During the clinical trial, 102 (82.3 %) patients underwent B-mode USI, and 22 (17.7 %) patients underwent USI with elastometry and elastography. USI results were compared with results of histological examination of cervical lymph nodes. Statistical evaluation of USI in different modes was performed.Results. B-mode USI was characterized by 88.2 % specificity, 0 % sensitivity, 80.4 % accuracy, and 44.1 % efficacy. Positive predictive value (PPV) was estimated as 0 %, and negative predictive value (NPV) as 90.1 %. USI with elastography was characterized by 100 % specificity, 83.3 % sensitivity, 95.5 % accuracy, and 91.7 % efficacy. PPV was estimated as 100 %, and NPV as 94.1 %. Threshold value of elastometry for diagnosis of occult metastases was 2.42 m/s with 83.3 sensitivity, and 87.5 % specificity. Method was characterized by 86.4 % accuracy, 85.4 efficacy, 71.4 % PPV and 93.3 % NPV.Conclusion. B-mode USI is characterized by low capability for diagnosis of subclinical regional metastases of squamous cell carcinoma of the oral mucosa. Elastometry and elastography offer a possibility to increase USI accuracy for diagnosis of subclinical regional metastases from 80 % to 86-95.5 % and efficacy from 44 % to 85–92 %.